2019
DOI: 10.1155/2019/7861297
|View full text |Cite
|
Sign up to set email alerts
|

Hericium erinaceus Improves Mood and Sleep Disorders in Patients Affected by Overweight or Obesity: Could Circulating Pro-BDNF and BDNF Be Potential Biomarkers?

Abstract: Epidemiological data indicate that subjects affected by obesity have an increased risk of developing mood disorders. The relationship between obesity and mood disorders is bidirectional. We assessed whether a Hericium erinaceus treatment improved depression, anxiety, sleep, and binge eating disorders after 8 weeks of supplementation in subjects affected by overweight or obesity under a low calorie diet regimen. Looking for a possible clinical biomarker, we assessed the serum balance between brain-derived neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 70 publications
2
32
1
1
Order By: Relevance
“…Based on toxicological and clinical studies, S. baicalensis, H. erinaceus and R. rosea are generally considered to be safe and well tolerated [40,[52][53][54][55][56][57][58][59][60][61][62][63]. In experimental studies, the estimated median lethal dose (LD 50 ) of some compounds varies according to the extraction method and administration route [54].…”
Section: S Baicalensis H Erinaceus and R Rosea: Toxicology And Nementioning
confidence: 99%
“…Based on toxicological and clinical studies, S. baicalensis, H. erinaceus and R. rosea are generally considered to be safe and well tolerated [40,[52][53][54][55][56][57][58][59][60][61][62][63]. In experimental studies, the estimated median lethal dose (LD 50 ) of some compounds varies according to the extraction method and administration route [54].…”
Section: S Baicalensis H Erinaceus and R Rosea: Toxicology And Nementioning
confidence: 99%
“…Recently, a clinical study examined the effects of H. erinaceus on anxiety, depression, binge eating, and sleep disorders in 77 volunteers with a body mass index (BMI) ≥ 25 kg/m 2 and an average age of 53.2 [80]. The study recruited overweight or obese participants positive for one or more administered tests, including Zung's Depression Self-Assessment Scale, Zung's Anxiety Self-Assessment Scale, Symptom Checklist-90, and the binge eating scale (BES).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The restoration effect of H. erinaceus on BDNF was suggested to be through monoaminergic modulation and normalization, as BDNF can be influenced by monoaminergic transmitters such as serotonin, norepinephrine, and dopamine [99]. A recent clinical study on patients with depression, anxiety, and sleep disorder examined the beneficial effects of 8 weeks of oral administration of capsules containing H. erinaceus extract (1200 mg/capsule, 3 capsules/day) [80]. They reported that pro-BDNF levels in the blood serum increased after 4 weeks of H. erinaceus administration, but there were no significant changes in serum BDNF levels.…”
Section: Bdnf Pathwaymentioning
confidence: 99%
See 2 more Smart Citations